Re-membering a Queer Body - Holmes, Morgan (UnderCurrents: Journal of Critical Environmental Studies, 1994)
In the spring 1993 issue of The Sciences, Brown University geneticist Anne Fausto-Sterling, citing the work of John Money, indicates that approximately four percent of the population is, to some degree, intersexual: they either possess physical characteristics of both officially recognized sexes or they have chromosomes which indicate a sex which are 'contradicted' by their physical appearance.1 In Toronto, the four percent figure translates into roughly 88,000 people. Yet little has been written about intersexuality, although its concerns often intersect with those of feminist and queer theory. This paper deals with feminist issues in patriarchal medicine and its relation(s) to intersexuality (and intersexuality's inherent ability to challenge arguments for the 'natural' basis of heterosexuality).
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme matérialiste; intersexuation; ontario; personnes intersexes; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2014; sociologie; thématiques; toronto; violences médicales

La peur de l'autre en soi: du sexisme à l'homophobie - Dorais, Michel; Dutey, Pierre; Welzer-Lang, Daniel (VLB, 1994)
Qu’est-ce que l’homophobie ? C’est l’appréhension de cette femme qui sommeille en chaque homme, de cet homme qui dort en chaque femme, de cet homosexuel ou cette homosexuelle qui, sait-on jamais, n’attend peut-être qu’à s’éveiller en nous.
Section: 302 pages : illustrations ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; québec; régions géographiques; shm4000; systèmes d'oppressions; thématiques

New feminist criticism: art, identity, action - Frueh, Joanna; Langer, Cassandra; Raven, Arlene; Frueh, Joanna; Langer, Cassandra; Raven, Arlene (IconEditions, 1994)
This anthology of fifteen timely articles offers a wide range of feminist criticism sparked by ideas and events of the 1980's and 1990's. The articles consider culture, language, race, identity, sexuality, gender, creativity, aging and other issues. Though different in methodology, the writings are united by their common interest in feminism as a vehicule for intellectual exploration and individual communication and understanding. In their revisionary approaches, the contributors offer exciting new insights into the complex interaction between women and cultures, questionning inclusion as well as exclusion. "New Feminist Criticism" presents the unfinished and ongoing agenda of feminism in art, society and culture.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; art contemporain; art féministe; arts; corps; cours; critique d'art; discipline; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; intersectionnalité; premier cycle; périodes historiques; race; thématiques; vieillesse

L'illusion transsexuelle - Mercader, Patricia (L'Harmattan, 1994)
Naît-on transsexuel ou le devient-on? Quel est le sexe des transsexuels? Peut-on parler de droit à l'identité sexuelle?.... En confrontant les points de vue des acteurs sociaux engagés dans le "phénomène transsexuel" (médecins, psychanalistes, sociologues, juristes et bien sûr les transsexuels eux-mêmes), cela éclaire les enjeux de société que traduisent ces questions profondément éthiques.
Section: 297 pages
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; postmodernisme; premier cycle; périodes historiques; queer; régions géographiques; sexe/genre; shm4000; systèmes d'oppressions; thématiques; transféminisme

The social construction of heterosexuality - Wilkinson, Sue; Kitzinger, Celia (Journal of Gender Studies, 1994)
Looks at some of the key issues raised by a tradition of social constructionist work on homosexuality, focusing on the nature of heterosexuality, heterosexual self-identification and the relationship between heterosexual sexual behavior and sexual identity. Political and theorectical importance of a sustained analysis of the functions and utility of heterosexuality; Impact of social constructionist theory on research relating to lesbians and gay men.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; cours; discipline; histoire et politique; premier cycle; psychologie; périodes historiques; sciences humaines; soc2014; sociologie; thématiques